2022
DOI: 10.3389/fped.2022.854324
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA as an Early Biomarker of Neonatal Sepsis

Abstract: Sepsis is a major cause of lethality in neonatal intensive care units. Despite significant advances in neonatal care and growing scientific knowledge about the disease, 4 of every 10 infants born in developed countries and suffering from sepsis die or experience considerable disability, including substantial and permanent neurodevelopmental impairment. Pharmacological treatment strategies for neonatal sepsis remain limited and mainly based upon early initiation of antibiotics and supportive treatment. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Nevertheless, these results most certainly cannot be directly extrapolated to neonatal patients with sepsis due to the widely different conditions, age, developmental stage, and overall state of the organism struck by neonatal sepsis ( 28 ). To the best of our knowledge, this present meta-analysis is the first reported investigation of the diagnostic value of suPAR in neonatal sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these results most certainly cannot be directly extrapolated to neonatal patients with sepsis due to the widely different conditions, age, developmental stage, and overall state of the organism struck by neonatal sepsis ( 28 ). To the best of our knowledge, this present meta-analysis is the first reported investigation of the diagnostic value of suPAR in neonatal sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…is was consistent with our study. ere have been many research studies looking for markers for the diagnosis and treatment of sepsis, including microRNAs, long noncoding RNAs, circular RNAs, pancreatic stone protein, and lipopolysaccharide-binding protein [26][27][28][29][30]. In our research, we identified 15 major hub genes (CCL5, CCR7, CD2, CD27, CD274, CD3D, GNLY, GZMA, GZMH, GZMK, IL2RB, IL7R, ITK, KLRB1, and PRF1) in the PPI network, and all of them were downregulated genes in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics explain why attempts to use TNF as an early marker of sepsis have failed. Generally, the determination of cytokines a few hours after infection initiation reveals high IL-6 values, whereas TNF is no longer detectable [ 185 ].…”
Section: Biomarkers Presently Used In Clinical Practicementioning
confidence: 99%